THE RELATIONSHIP BETWEEN OBESITY AND DIABETES - Usanov Quvonchbek Rasul o’g’li, (TADQIQOTLAR, 2026)
Abstract: The prevalence of both conditions has risen dramatically over recent decades,  largely  driven  by  sedentary  lifestyles,  unhealthy  dietary  patterns,  and urbanization.  Numerous  scientific  studies  have  established  a  strong  and  complex relationship between obesity and the development of diabetes, making obesity one of the primary modifiable risk factors for this metabolic disorder. Obesity is characterized by excessive accumulation of body fat, which negatively affects metabolic processes in the body. One of the key mechanisms linking obesity to diabetes is insulin resistance. These biochemical changes impair the body’s ability to use insulin effectively, leading to  elevated  blood  glucose  levels.  Furthermore,  chronic  low-grade  inflammation associated with obesity plays a crucial role in disrupting insulin signaling pathways. The  enlargement  of  fat  cells  and  infiltration  of  immune  cells  into  adipose  tissue contribute  to  systemic  inflammation,  which  exacerbates  metabolic  dysfunction.  In conclusion, obesity and diabetes are closely interconnected conditions with shared risk factors  and  underlying  mechanisms.  Addressing  obesity  through  lifestyle modifications,  including  balanced  diet,  regular  physical  activity,  and  behavioral changes, is crucial in preventing and managing diabetes. Public health interventions and increased awareness are vital to combat the growing epidemic of these diseases and improve overall population health.